Synthesis of renewable alkylated decalins with p-quinone and 2-methyl-2, 4-pentanediol. Issue 3 (11th January 2022) - Liu, Chunwei; Hu, Yancheng; Li, Guangyi; Wang, Aiqin; Cong, Yu; Wang, Xiaodong; Zhang, Tao; Li, Ning
Abstract : Alkylated decalins were first produced by the dehydration of 2-methyl-2, 4-pentanediol, followed by Diels–Alder reaction with p -quinone and the hydrodeoxygenation. Abstract : Decalins are the main component of JP-900, a coal-based thermal stable advanced aviation fuel. Meanwhile, these compounds are also widely used as additives to improve the volumetric heat value and thermal stability of aviation fuels. Herein, a brand new three-step route was developed for the synthesis of renewable alkylated decalins from 2-methyl-2, 4-pentanediol (MPD) and p -quinone, two platform compounds that can be derived from lignocellulose. First, a mixture of C6 dienes was obtained from the dehydration of 2-methyl-2, 4-pentanediol under the catalysis of choline chloride (ChCl) based acidic deep eutectic solvents (DES). Among the investigated reaction media, the ChCl/MSA DES prepared with ChCl and methanesulfonic acid (MSA) demonstrated the highest activity and selectivity for the dehydration of MPD. This can be rationalized by the relatively higher acid strength of the MSA. By the Diels–Alder reaction of C6 dienes and p -quinone, C12 cycloadducts with double six-membered ring carbon chain structures were formed in the absence of any catalyst. Finally, the C12 cycloadducts were further hydrodeoxygenated to alkylated decalins with high-density (0.91 g mL −1 ) and low freezing point (225–236 K) over a physical mixture of Pd/C and H-Y zeolite.